A comparison between psychological and economic factors affecting individual investor's decision-making behavior - Aamir Sarwar; Ghadeer Afaf (Cogent Business & Management, 2016)
The purpose of this study was to understand and determine the difference between the effects of Psychological and Economic factors on individual investor's decision-making. To achieve this purpose, questionnaire was used as an instrument to gather primary data from the investors of stock exchange using convenient sampling. Total numbers of responses collected were 254. Factor analysis was applied to find out major contributing components of psychological and economic factors. Main components of psychological factors were contributing 61.671% variance to it and components of economic factor were contributing 56.697% variance to it. Findings show that there is significant relationship of psychological factors and economic factors with individual investor's decision-making. Regression analysis shows that psychological factors as compared to economic factors have more effect on decision-making behavior. Results of t-test showed that there is no significant relationship between the gender and investment decision-making. Results of one-way ANOVA test showed significant relationship between monthly income level of investors and investment decision-making.
Keywords: 650